"The Dark side of Hope": Genre and Globalization in The Hunger Games. Issue 2 (July 2017) - Kurtz, Malisa
Abstract : The global popularity of Suzanne Collins's The Hunger Games has sparked a wide variety of reactions: schools have introduced the books to their curriculum, there are numerous summer camps based on the series, and academic anthologies have emerged focusing on the trend of adolescent dystopias. Because of The Hunger Games ' "merely generic" narrative and its adaptation to Hollywood blockbuster, however, critical examinations of the trilogy so far have been primarily confined to discussions of young adult fiction and adaptation theory. Resisting such readings, this essay will focus on the film's popularity in the context of Thailand, exploring how genres can be a useful starting point for exploring both the local effects of globalization as well as the material conditions we might share across diverse sociocultural contexts.